Dual‐mode bandpass substrate integrated waveguide filter with a complementary split ring resonator. Issue 3 (5th February 2018) - Guo, Hui; An, Xiang; Lv, Zhi‐Qing
Abstract: We present a new bandpass filter by combining an isosceles right‐triangle substrate integrated waveguide (SIW) cavity with a complementary split ring resonator (CSRR) together. The first and second modes of the SIW cavity are used to form a desirable passband with the help of a perturbation metallic via‐hole. We introduce a CSRR at the ground plate of the SIW cavity to produce two controllable transmission zeros at the upper stopband, which improve the upper stopband characteristic greatly. Moreover, at the lower stopband, we make use of a pair of T‐shape stub‐loaded resonators to generate a transmission zero, and thus improve the out‐of‐band rejection greatly. To validate our design scheme, a filter sample has been fabricated and measured. The measured results and simulation ones are in good agreements. The filters show advantages of compactness, sharp stopband rejection, high frequency‐selectivity, and controllable passband and transmission zeros.